Maxillofacial fractures surgically treated: a 3-year experience of a Cuban hospital - Ibraín E. Corrales-Reyes (Permanyer, 2021)
Aim: The aim of the study was to characterize the maxillofacial fractures surgically treated in a Cuban hospital. Materials and methods: This was a descriptive and retrospective cross-sectional study based on the medical records of patients attended between January 1, 2017 and December 31, 2019 in the Maxillofacial Surgery Department of Carlos Manuel de Céspedes General University Hospital, Cuba. Age, gender, residency, municipality, etiology, month and year of trauma, number and type of fractures, and alcohol consumption at the time of trauma were recorded. Results: 126 cases and 304 fractures were investigated. Males were the most affected (n = 115; 91.27%). The main etiology was interpersonal violence (IPV) (46.03%). Seventy-one (56.35%) patients had zygomatico-maxillary complex fractures. In the multivariate analysis, alcohol consumption was significantly lower as the age increased (aPR: 0.989; confidence interval [CI] 95%: 0.979-0.99; p = 0.026), as well as in those patients who lived in urban zones (aPR: 0.57; CI 95%: 0.44-0.74; p < 0.001), adjusted by the side of the fracture and the municipality. Conclusions: The profile of the maxillofacial fractures in this Cuban hospital seems to be mixed by age, affecting young people and the elderly. IPV was the major cause of maxillofacial fractures, while zygomatico-maxillary complex bones and mandible were the most affected maxillofacial areas.